Criteria system of formation of spectral channels of multichannel radiation thermometer - Гоц, Наталія Євгенівна (Technology audit and production reserves, 2015)
Today, methods for measuring the radiation temperature depending on the number of spectral bands that used for their implementation can be divided into single-band and multi-band. Development of multi-band methods is perspective for measuring radiation temperature because their use is aimed at reducing the methodical error of measurement of radiation temperature through the use of spectral information of radioactive properties of the object. For its current implementation it is actual the development of multi-radiation thermometers with multiple spectral channels. To implement the multi-channel methods by multi-channel radiation thermometers it is proposed set of criteria for the formation of spectral channels: criteria for forming signal of separate spectral channel; criteria of relative position of spectral channels; criteria for selection of spectral channels, depending on the method of multi-channel radiation thermometry. Requirements for the implementation of these criteria are formed. As a result, we can say that requirements based on defined criteria are formulated for spectral bands of radiation thermometer and determined the optimal parameters of spectral channels of multi-channel radiation thermometer used in a spectral and temperature range and implements appropriate methods for measuring the radiation temperature. The implementation of these requirements together optimally determine the parameters of spectral channels of multi-channel radiation thermometer, which operates in a spectral and temperature range and implements appropriate methods for measuring the radiation temperature.